Machiavellian Marketing And Digital Deception: A Bibliometric Analysis Of Dark Triad Traits, Manipulation, And Misinformation In Social Media (1969-2025) - Pilifus Junianto; Agustinus Purna Irawan; Muhammad Idrus Taba; Brigida Endah Nuraeni; Edi Sumarya (UNIVED Press, 2025)
This study systematically maps the intellectual structure of research on Machiavellian marketing and digital deception, examining intersections between dark personality traits, manipulation, and social media misinformation. Employing bibliometric analysis, 2,512 journal articles from Scopus database (1969-October 2025) were analyzed using VOSviewer software. Three complementary techniques were applied: co-citation analysis revealing foundational knowledge structures, bibliographic coupling identifying current research themes, and co-word analysis predicting future trends. Four distinct research clusters emerged: ethical governance and digital persuasion, social psychology and behavioral impacts, misinformation dynamics and societal effects, and technology-driven detection and prevention. The analysis revealed 84,394 citations with h-index of 122, demonstrating substantial scholarly impact. Key trends include AI-behavioral science integration, deepfake detection, emotional manipulation, and dark triad influences in digital contexts. This research provides the first comprehensive bibliometric synthesis integrating Machiavellian traits with digital deception and misinformation, offering systematic roadmap for interdisciplinary investigations.